SIFAT FISIKA TANAH ALUVIAL PADA SAWAH TADAH HUJAN TANPA DAN DENGAN OLAH TANAH DI DESA TEMPURUKAN KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Darwin, Darwin (Fakultas Pertanian Universitas Tanjungpura, 2016)
ABSTRACK This study aims to determine differences in physical properties of the soil in rainfed with and no tillage at Tempurukan village of Muara Pawan subdistrict of Ketapang regency. The study was conducted in January and March 2016, this research using field survey methods to conduct observations and sampling of soils, in rainfed areas with rice vegetation on three locations, namely at the location A no-tillage (5-10 years) , location B with tillage (10-15 years), and the location C with tillage (20-25 years). Variable observations include: soil physical properties (texture, aggregate stability, bulk density, porosity and moisture content of field capacity), then supporting variable (pH, organic C, total-N and C / N ratio). The results showed the soil texture is generally dominated by the clay fraction and classified into class dusty clay texture, different aggregate stability at a depth of 0-20 cm, while the depth of 20-40 cm aggregate value of all 100%, the highest bulk density on the location of no tillage on depth of 0-20 cm and 20-40 cm, orthogonal contrast test showed highly significant at a depth of 0-20 cm, increasing porosity classified among the rice fields of untreated degan treated soil and duration management fields, field capacity water content tends to increase because of the high clay fraction so that the soil's ability to pass water is also low, slightly acid soil pH that is classified (from 5.6 to 6.5), C-organic classified as very low to moderate, namely (from 0.23 to 2.16), N-total are classified as moderate (0.21 to 0.50), C/N ratio is relatively very low to low, (4.60 to 8.71).